A Multilevel Governance and Growth Management: The Use of Impact Fees by Florida Cities. (November 2014) - Lee, Youngmi; Feiock, Richard C.; Lee, In Won
The use of local impact fees is examined as a product of governmental supply and community demands in a political market. Whereas new regionalism emphasizes the embeddedness of city-level decisions in a regional context, political market theories and the empirical study of local growth decisions treat city decisions as being shaped by local conditions, institutions, and processes. Hierarchical general linear modeling provides a statistical method to examine influences on policy decisions at multiple levels. This article estimates a hierarchical general linear model that captures the impact of political market forces and control variables on the enactment or continuation of impact fees. The likelihood of using impact fees varies across metropolitan areas, and intergovernmental revenue facilitates local innovation, but larger council size is a barrier to application of this policy innovation. The conclusion provides a research approach and agenda for practitioners and scholars to better understand multilevel governance and its implications for policy choice.